Domestication of marine rotifer proales similis in extensive culture system at different salinities / Nor Syahirah Shaharudin - Shaharudin, Nor Syahirah (2020)
In the aquaculture industry, Proales similis is commonly use to feed fish larvae and crustacean larvae. One of the factor that influences the production of seawater rotifer is microalgae named Nannochloropsis sp. This experiment was conducted to determine the effect of different salinities start with 15 ppt, 20 ppt, 25 ppt and 30 ppt towards the growth rate of seawater rotifer Proales similis available at Pulau Sayak, Kedah. The possibility of obtaining high density cultures of the seawater rotifer Proales similis was observed. Nannochloropsis sp. was uesd as feed thus will give nutrient towards seawater rotifer Proales similis to keep on growing and survive. Isolation method and batch culture method was used in this study. Isolation method was used to get the pure culture of seawater rotifer Proales similis while batch culture method was used to produce the mass production of seawater rotifer Proales similis. An expected result, the growth rate of seawater rotifer Proales similis can continuously live at all different salinity level 15 ppt, 20 ppt, 25 ppt and 30 ppt.